Phenotypic/Genotypic Profile of Children with Neuronal Ceroid Lipofuscinosis in Southern Brazil - Santos, Berkmis Viana; de Souza, Josiane; Zeny, Michelle Silva; Santos, Mara Lúcia Schmitz Ferreira; do Valle, Daniel Almeida (Neuropediatrics, 2024)
Introduction Neuronal ceroid lipofuscinoses (CLNs) are a group of lysosomal storage disorders of genetic origin, characterized by progressive neurodegeneration and intracellular accumulation of autofluorescent lipopigment. Thirteen genes related to CLNs are currently described, showing genetic and allelic heterogeneity, most of them with an autosomal recessive pattern. Due to the few descriptions of cases related to CLNs in Brazil, it is necessary to describe the phenotypic and genotypic characteristics of these patients. This study aims to evaluate the genotypic profile and correlate it with the phenotypic characteristics of patients with CLN in a children's hospital.Methods This study was performed as a descriptive cross-sectional study with analysis of medical records, imaging, and laboratory tests of patients who had a confirmed molecular diagnosis of CLN.Results The sample consisted of 11 patients from nine families with different subtypes of CLNs (CLN2, 5, 6, 7, and 8), with CLN2 being the most prevalent in the study. A total of 16 mutation variants were identified in genes associated with the five CLNs described in this study, with typical and atypical clinical phenotypes depending on the subtype and its variants.Conclusion Novel mutations identified in the patients in this study showed phenotypes of rapid and severe progression in the CLN2 patient and similar characteristics in CLN6 and CLN7 patients, as previously described in the literature.
Keywords: ceroid lipofuscinosis; neuronal; genetic association studies; children